Investigating Achilles and patellar tendinopathy prevalence in elite athletics - Janssen, I.; van der Worp, H.; Hensing, S.; Zwerver, J. (Research in Sports Medicine, 2018)
Although injury surveillance in athletics is routinely conducted, discipline-specific Achilles and patellar tendinopathy prevalence remains unknown. The purpose of this study was to explore discipline-specific tendinopathy prevalence and identify whether injury-specific risk factors differed in athletes. Elite athletes were recruited and provided information on their sport training including Achilles and patellar tendon pain history. In order to ascertain whether between-discipline differences existed, data were categorized into discipline groups. Middle-distance athletes reported the highest prevalence of Achilles tendinopathy and the combined athletes reported the highest patellar tendinopathy prevalence. Greater calf stiffness was reported in athletes who experienced Achilles tendinopathy compared to those who did not. A substantial portion of athletes believed their performance decreased as a result of their tendon pain. In order to develop discipline-specific evidence-based injury prevention programmes, further discipline-specific research is required to quantify the mechanism for Achilles and patellar tendinopathy development in elite athletics.